Geopolitics behind the COVID-19 pandemic. Book Review: Coronavirus Politics: The comparative Politics and Policy of COVID-19 - Zamora-Steller, Sandy (2022)
The book Coronavirus Politics: The comparative Politics and Policy of COVID-19  analyzes how elements of power are directly related to the measures implemented by governments to face the pandemic of COVID-19. And how these elements conditioned the development of the pandemic in different regions worldwide. Then, the book uses individual study cases for the different geographical regions, this allows for contextualized reflections where people living in the studied regions deepen on the reactions of their governments.